500 V breakdown voltage in β‐Ga2O3 laterally diffused metal‐oxide‐semiconductor field‐effect transistor with 108 MW/cm2 power figure of merit - Nesa Abedi Rik; Ali. A. Orouji; Dariush Madadi (IET Circuits, Devices and Systems)
Abstract The authors’ present a silicon‐on‐insulator (SOI) laterally diffused metal‐oxide‐semiconductor field‐effect transistor (LDMOSFET) with β‐Ga2O3 , which is a large bandgap semiconductor (β‐LDMOSFET), for increasing breakdown voltage (VBR) and power figure of merit. The fundamental purpose is to use a β‐Ga2O3 semiconductor instead of silicon material due to its large breakdown field. The characteristics of β‐LDMOSFET are analysed to those of standard LDMOSFET, such as VBR, ON‐resistance (RON), power figure of merit (PFOM), and radio frequency (RF) performances. The effects of RF, such as gate‐drain capacitance (CGD), gate‐source capacitance (CGS), transit frequency (fT), and maximum frequency of oscillation (fMAX) have been investigated. The β‐LDMOSFET structure outperforms performance in the VBR by increasing it to 500 versus 84.4 V in standard LDMOSFET design. The suggested β‐LDMOSFET has RON ~ 2.3 mΩ.cm−2 and increased the PFOM (VBR2/RON) to 108.6 MW/cm2. All the simulations are done with TCAD and simulation models are calibrated with the experimental data.